Spinal Interleukin-1β Inhibits Astrocyte Cytochrome P450c17 Expression Which Controls the Development of Mechanical Allodynia in a Mouse Model of Neuropathic Pain - Choi, Sheu-Ran; Han, Ho-Jae; Beitz, Alvin J.; Lee, Jang-Hern (Frontiers in Molecular Neuroscience, 2019)
We have recently demonstrated that sciatic nerve injury increases the expression of spinal cytochrome P450c17, a key neurosteroidogenic enzyme, which plays a critical role in the development of peripheral neuropathic pain. However, the modulatory mechanisms responsible for the expression of spinal P450c17 have yet to be examined. Here we investigated the possible involvement of interleukin-1β (IL-1β) in altering P450c17 expression during the induction phase of neuropathic pain. Neuropathic pain was produced by chronic constriction injury (CCI) of the right sciatic nerve in mice and mechanical allodynia was evaluated in the hind paws using a von-Frey filament (0.16 g). Western blotting and immunohistochemistry were performed to assess the expression of spinal IL-1β, interleukin-1 receptor type 1 (IL-1R1), P450c17, and GFAP. Spinal IL-1β was significantly increased on day 1 post-surgery and its receptor, IL-1R1 was expressed in GFAP-positive astrocytes. Intrathecal administration of the recombinant interleukin-1 receptor antagonist (IL-1ra, 20 ng) on days 0 and 1 post-surgery enhanced GFAP expression on day 1 post-surgery and induced an early increase in P450c17 expression in astrocytes, but not in neurons. Administration of IL-1β (10 ng) on days 0 and 1 post-surgery blocked the enhancement of both spinal P450c17 and GFAP expression induced by IL-1ra (20 ng) administration. Intrathecal administration of IL-1ra (20 ng) on days 0 to 3 post-surgery also facilitated the CCI-induced development of mechanical allodynia, and this early developed pain was dose-dependently attenuated by the administration of the P450c17 inhibitor, ketoconazole (1, 3 or 10 nmol) or the astrocyte metabolic inhibitor, fluorocitrate (0.01, 0.03 or 0.1 nmol). These results demonstrate that early increases in spinal IL-1β temporally inhibit astrocyte P450c17 expression and astrocyte activation ultimately controlling the development of mechanical allodynia induced by peripheral nerve injury. These findings imply that spinal IL-1β plays an important role as an early, but transient, control mechanism in the development of peripheral neuropathic pain via the inhibition of astrocyte P450c17 expression and astrocyte activation.